Moriarty's Ghost: Or the Queer Disruption of the BBC's Sherlock. (July 2015) - Fathallah, Judith
This article argues that the BBC's Sherlock is outwardly a conservative text sedimenting the historical function of Sherlock Holmes as a model of hegemonic British masculinity. However, queer disruptions in the performance of masculinity may be read as, after Butler, destabilizing and revealing the groundlessness of gender constructions. For as Butler has argued, hetero-masculine performativity is "constantly haunted by that domain of sexual possibility that must be excluded for heterosexualized gender to produce itself." Referencing Laclau's perception of "hauntologies" to texts (adapted from Derrida), I posit that the presence/specter of the queer villain Moriarty can be read as a caesura challenging performed hegemonic masculinity. With the possible death and promise of Moriarty's return at the close of the current season, the series now stands at a crossroads. It may either revert to the queerbaiting of previous seasons or foreshadow a more radical text.